(NpOSOBIE PO TEHNI^ESKOMU PEREWODU S FRANCUZSKOGO QZYKA (B:s (NdLQ NEQZYKOWYH WUZOW (B/s - (NkORVAWIN(B, (NaRKADIJ wASILXEWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1977)
(NbIBLIOGR(B. (NS(B. 317-319, (NI BIBLIOGR(B. (NW TEKSTEs
Keywords: (NtEHNI^ESKAQ LITERATURAs; (NfRANCUZSKIJ QZYK (B- (NpEREWODYs